2022
DOI: 10.3389/fanim.2022.782507
|View full text |Cite
|
Sign up to set email alerts
|

Water for Domestic Ducks: The Benefits and Challenges in Commercial Production

Abstract: Although we have been farming ducks for at least 4,000 years, with some accounts suggesting domestication having begun more than 38,000 years ago, there are still many unknowns for optimizing domestic duck welfare in a commercial setting. Ducks being waterfowl, are semi-aquatic and have unique behavioral needs when compared to other commonly farmed poultry species. Providing ducks with open water which allows for full body immersion so that they may perform their full repertoire of water-related behaviors is i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(26 citation statements)
references
References 77 publications
0
26
0
Order By: Relevance
“…Therefore, a good weight gain was found in duck care with pools. Likewise, the opinion of Babington and Campbell (2022) stated that Ducks like areas or edges of water for resting, standing, and foraging simultaneously with other ducks, such as lakes or pools. Similarly, Pangemanan et al (2019) explained that ducks released in rivers or swamps usually look for feed in the form of snails or other small insects.…”
Section: Weight Gainmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, a good weight gain was found in duck care with pools. Likewise, the opinion of Babington and Campbell (2022) stated that Ducks like areas or edges of water for resting, standing, and foraging simultaneously with other ducks, such as lakes or pools. Similarly, Pangemanan et al (2019) explained that ducks released in rivers or swamps usually look for feed in the form of snails or other small insects.…”
Section: Weight Gainmentioning
confidence: 99%
“…Ducks are semi-aquatic animals that under natural conditions will spend a large part of their lives in or around water (Babington and Campbell, 2022). Ducks need sufficient clean water to drink, dip their whole head so that it becomes clear and avoid stuffy noses with feed and mud Besides, the pond also lowers the body temperature when the environment is hot (Nicol et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The standard recommendations of the Standing Committee of the European Convention for the Protection of Farm Animals suggest that when raising geese indoors, open water sources should be provided as much as possible even in the absence of a pool [ 13 ]. Moreover, recent studies have demonstrated that water-related behaviors are irreplaceable for waterfowl [ 13 , 14 , 15 , 16 , 17 ]. Open water sources can enhance the well-being and behavior of waterfowl, such as ducks and geese.…”
Section: Introductionmentioning
confidence: 99%
“…Open water sources can enhance the well-being and behavior of waterfowl, such as ducks and geese. Furthermore, they can improve scoring indicators, such as feather quality; feather, eye, and nostril cleanliness; gait; and footpad dermatitis [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ]. However, a water pool is a crucial medium through which ducks can transmit avian influenza virus [ 25 , 26 , 27 ]; when they drink, dabble, or preen in virus-contaminated pools, they may become infected, posing a high biosecurity threat to poultry farms.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation